Site‐Specific Loading at the Fifth Metatarsal Base in Rehabilitative Devices: Implications for Jones Fracture Treatment. Issue 11 (28th May 2014) - Hunt, Kenneth J.; Goeb, Yannick; Esparza, Rolando; Malone, Maria; Shultz, Rebecca; Matheson, Gordon
Abstract : Background: Fractures of the fifth metatarsal base are a relatively common injury. Whether treated surgically or nonsurgically, injury rehabilitation typically involves immobilization in a rigid sandal or short controlled ankle movement (CAM) walker boot. Objective: To determine the peak pressure, contact pressure, and impulse at the base of the fifth metatarsal in 3 common footwear devices during common gait activities. Design: This was a retrospective comparative study. Setting: Research was conducted in a sports performance laboratory at a university. Participants: Twenty subjects without a recent history of foot injuries volunteered to participate. Methods: Each subject performed 3 common gait activities (walking, heel walking, and pivoting) in 3 footwear devices (short CAM walker boot, postoperative sandal, running shoe). Pressure data were sampled (100 Hz) using individually sized plantar pressure insoles and software (Tekscan). Walking trials were collected at 1.0 m/s ± 5% (FusionSport Timing Gates). Outcome Measurements: Peak pressure, contact pressure, and impulse at the fifth metatarsal base region were determined for all trials for all subjects. Mixed‐effect regression models were used to compare pairwise differences in outcome variables between footwear devices. Results: The CAM walker boot resulted in significantly lower peak pressure at the fifth metatarsal during walking and heel‐walking relative to the postoperative sandal ( P < .01) and during heel‐walking ( P < .01) relative to the standard athletic shoe. The CAM walker boot significantly reduced contact pressures at the fifth metatarsal during walking and heel‐walking relative to the postoperative sandal ( P < .01), and during heel‐walking relative to the standard athletic shoe ( P < .001). Conclusions: Our results suggest that the short CAM walker boot more effectively offloads the fifth metatarsal during common gait activities than a postoperative sandal or a standard athletic shoe. A short CAM walker boot may be a beneficial rehabilitative tool for patients undergoing rehabilitation after treatment of Jones fractures and other base of fifth metatarsal fractures.